The Effectiveness of Eca Aura as Brand Ambassador for Derma Angel Among the People of Surabaya - Natasya Nethania Nava Djianto; Lady Joanne Tjahyana; Chory Angela Wijayanti (Journal of Content and Engagement, 2025)
This study aims to measure the effectiveness of Eca Aura as a Brand Ambassador for Derma in the marketing public relations (MPR) strategy of the Derma Angel brand in Surabaya City. A Brand Ambassador is an individual who represents a brand and serves as a communication bridge between the brand and the public. In implementing its marketing public relations strategy, Derma Angel appointed Eca Aura as Brand Ambassador to help build communication and increase brand awareness among audiences, as well as establish a positive image for the Derma Angel brand. This study employed a survey method by collecting data through questionnaires, which were distributed to 400 respondents who are residents of Surabaya City using a Likert scale. The findings of this study indicate that Eca Aura is effective as Derma Angel's Brand Ambassador based on the VisCAP indicators, with attractiveness being the most effective indicator among the four indicators. An interesting finding in this study relates to the Visibility indicator, as traditional media such as banners proved to be more effective than online media in enhancing visibility.